Process Predictors of the Outcome of Group Drug Counseling - Crits-Christoph, Paul (2012)
OBJECTIVE: This study examined the relation of process variables to the outcome of group drug counseling, a commonly used community treatment, for cocaine dependence. METHOD: Videotaped group drug counseling sessions from 440 adult patients (23% female, 41% minority) were rated for member alliance, group cohesion, participation, self-disclosure, positive and non-positive feedback and advice, during the 6-month treatment of cocaine dependence. Average, session-level, and slopes of process scores were evaluated. Primary outcomes were monthly cocaine use (days using out of 30), next session cocaine use, and duration of sustained abstinence from cocaine. Secondary outcomes were endorsement of 12-step philosophy and beliefs about substance abuse. RESULTS: More positive alliances (with counselor) were associated with reductions in days using cocaine per month and next-session cocaine use, and increases in endorsement of 12-step philosophy. Patient self-disclosure about the past and degree of participation in the group were generally not predictive of group drug counseling outcomes. More advice from counselor and other group members were consistently associated with poorer outcomes in all categories. Individual differences in changes in process variables over time (linear slopes) were generally not predictive of treatment outcomes. CONCLUSIONS: Some group behaviors widely believed to be associated with outcome, such as self-disclosure and participation, were not generally predictive of outcomes of group drug counseling, but alliance with the group counselor was positively associated, and advice giving negatively associated, with the outcome of treatments for cocaine dependence.